The Impact of Work Stress on the Psychological Well-being of Public Elementary School Teachers - Alegre, Emybel M.; Labajo, Jomarie Kae M. (International Journal of Membrane Science and Technology, 2023)
This study aimed to explore the impact of work stress on the psychological well-being of the public elementary school teachers. The sample consists of 60 out of 75 teachers from the three public elementary schools located in the municipality of Barobo, Surigao del Sur. The study utilized a correlation and regression research design. Results revealed that teachers find their job relatively relaxed due to their students’ behavior and can maintain a positive attitude and focus on their teaching goals. Moreover, positive working relationships between teachers and administrators can help reduce teacher stress levels. Results further revealed that there is a strong positive correlation between the work stress and the psychological well-being of the public elementary school teachers, and this correlation is statistically significant. However, regression analysis revealed that the work stress of these teachers did not have a significant impact on their psychological well-being. Consequently, the above results implied that work stress did not predict the psychological well-being of public elementary school teachers.